Botulinum Toxin and Its Contribution to the Treatment of Masseteric Hypertrophy - R. Jurkovič; P. Macák (Czech Dental Chamber, 2005)
With discovery and use of botulinum toxin masseteric hypertrophy has become treatable in a minimal invasive way. The authors discuss the masseteric hypertrophy as such as well as they describe a technique of clinical application of botulinum toxin in its therapy. They introduce a significant contribution of botulinum toxin to patients with masseteric hypertrophy.